1997
DOI: 10.1103/physrevd.55.6877
|View full text |Cite
|
Sign up to set email alerts
|

Preequilibrium evolution of a non-Abelian plasma

Abstract: We study the production and the equilibration of a non-Abelian qq plasma in an external chromoelectric field, by solving the Boltzmann equation with the non-Abelian features explicitly incorporated. We consider the gauge group SU (2) and show that the colour degree of freedom has a major and dominant role in the dynamics of the system. It is seen that the assumption of the so called Abelian dominance is not justified. Finally, it is also shown that many of the features of microscopic studies of the system appe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…The above set of invariant variables also serve to express the source terms for qq and gluon pairs which will be obtained by the Schwinger mechanism. The expression for qq production (obtained from constant electric field) is written as [11] …”
Section: The Flux-tube Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The above set of invariant variables also serve to express the source terms for qq and gluon pairs which will be obtained by the Schwinger mechanism. The expression for qq production (obtained from constant electric field) is written as [11] …”
Section: The Flux-tube Modelmentioning
confidence: 99%
“…In a recent paper [11] we studied the evolution of a non-abelian qq plasma in the context of color flux-tube model, where it was shown that the non-abelian features have a major role in the evolution of the system in a manner that was not captured in any of the earlier studies [7,8,12] which were purely abelian in their content. It was also argued that it was unlikely that the system would equilibrate instantaneously.…”
Section: Introductionmentioning
confidence: 99%
“…That can have a significant impact on the evolution of the plasma, promoting plasma oscillations [29], and also on its subsequent hadronisation [30]. Perhaps the most significant defect of our study is the use of an Abelian model for the colour fields and progress with a non-Abelian transport equation would be a marked improvement [19].…”
Section: Epiloguementioning
confidence: 99%
“…However, its complexity mitigates against its use in semi-quantitative, exploratory studies and hence herein we employ a simple RTA [14,15,18,19,20,21,22,23].…”
Section: Equilibrating Collisionsmentioning
confidence: 99%
See 1 more Smart Citation